2017
DOI: 10.1177/2378023117718122
|View full text |Cite
|
Sign up to set email alerts
|

“Super Bowl Babies”: Do Counties with Super Bowl Winning Teams Experience Increases in Births Nine Months Later?

Abstract: Following the claim of a highly publicized National Football League (NFL) commercial, we test whether the Super Bowl provides a positive exogenous shock to fertility in counties of winning teams. Using stadium locations to identify teams’ counties, we analyze the number of births in counties of both winning and losing teams for ten recent Super Bowls. We also test for state effects and general effects of the NFL playoffs. Overall, our results show no clear pattern of increases in the number of births in winnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Two previous academic articles on the effect of sport events on fertility have produced contradictory findings. The anecdotal claim of an "Iniesta generation" following the last-minute goal by the Barcelona midfielder in the UEFA Champions league semifinal against Chelsea is confirmed by Montesinos et al (2013), while no evidence of "Super Bowl Babies" is found by Hayward and Rybińska (2017). What these two studies have in common is that they both focus on the supposed positive effect of success in a major sport event on fertility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two previous academic articles on the effect of sport events on fertility have produced contradictory findings. The anecdotal claim of an "Iniesta generation" following the last-minute goal by the Barcelona midfielder in the UEFA Champions league semifinal against Chelsea is confirmed by Montesinos et al (2013), while no evidence of "Super Bowl Babies" is found by Hayward and Rybińska (2017). What these two studies have in common is that they both focus on the supposed positive effect of success in a major sport event on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Montesinos et al (2013) document a spike in fertility in the Barcelona area nine months after a dramatic goal scored by Iniesta against Chelsea in the last minute of the semifinal of the UEFA Champions League in 2009, in line with anecdotal evidence reported in the Spanish news. 1 On the other hand, Hayward and Rybińska (2017) find that the Super Bowl does not produce an increase in the number of birth in the counties of winning teams nine months later, contrary to the anecdotal evidence in the news and a widely broadcasted NFL announcement. 2 In this article, we test the hypothesis that mood shocks influence fertility behavior, by studying the effect of unexpected results of soccer games in Spain on the number of births nine months thereafter.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations